2008
DOI: 10.1038/ni.1623
|View full text |Cite
|
Sign up to set email alerts
|

PTEN functions to 'prioritize' chemotactic cues and prevent 'distraction' in migrating neutrophils

Abstract: Neutrophils encounter and 'prioritize' many chemoattractants in their pursuit of bacteria. Here we tested the possibility that the phosphatase PTEN is responsible for the prioritization of chemoattractants. Neutrophils induced chemotaxis by two separate pathways, the phosphatidylinositol-3-OH kinase (PI(3)K) phosphatase and tensin homolog (PTEN) pathway, and the p38 mitogen-activated protein kinase pathway, with the p38 pathway dominating over the PI(3)K pathway. Pten(-/-) neutrophils could not prioritize chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
222
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(232 citation statements)
references
References 38 publications
9
222
0
1
Order By: Relevance
“…The co-existence of these redundant pathways allows cells greater flexibility to respond to different environmental circumstances, such as gradients of high or low steepness. In mammalian cells, it is also reported that PLA plays a role in neutrophil chemotaxis to fMLP, but not to CXCL8 (41). We show here that the SFK pathway functions in parallel to PI3K in determining the directional cell movement in response to a CXCL8 gradient.…”
Section: Discussionmentioning
confidence: 52%
“…The co-existence of these redundant pathways allows cells greater flexibility to respond to different environmental circumstances, such as gradients of high or low steepness. In mammalian cells, it is also reported that PLA plays a role in neutrophil chemotaxis to fMLP, but not to CXCL8 (41). We show here that the SFK pathway functions in parallel to PI3K in determining the directional cell movement in response to a CXCL8 gradient.…”
Section: Discussionmentioning
confidence: 52%
“…Neutrophils prioritize between different chemoattractant cues, favoring p38-controlled migration toward bacterial end targets over PI3K-controlled migration toward endogenous chemoattractants (42). Priorization is regulated by the phosphatase and tensin homolog (PTEN) (43), which inhibits chemoattractant-derived PI3K signaling, allowing unidirectional migration to an end-target chemoattractant. It is possible that GRP and IL-8 are viewed by neutrophils as equivalent chemoattractants, and the blockage of either receptor in the presence of the other's agonist inhibits the PI3K pathway, inhibiting migration toward the other molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PTEN in chemotaxis has been somewhat controversial, with some studies suggesting a role for PTEN in directionality or migration and others finding PTEN to be dispensable for chemotaxis. [39][40][41] These discrepancies likely reflect differences in experimental setup, such as in vitro versus in vivo studies, differences in chemoattractant gradients, and the activation state of cells. In addition, the time frame of observation is important.…”
Section: Discussionmentioning
confidence: 99%